A personal leadership statement (2023)
Leadership is a dynamic and ethical process that effectively influences others to achieve goals. From this perspective, leadership is considered as a challenging task that necessitates the utilization of ethical values, moral principles, and well-being. This paper describes the definition of moral leadership, analyses our assumptions, explores the concept of leadership empowerment and its implications for the future. It also emphasizes the importance of critical thinking, ethical decision-making skills and working collaboratively to establish a positive and supportive learning community. Additionally, the paper examines the role of leadership empowerment in educational settings, highlighting the importance of collaboration among leaders and followers to foster a positive school climate, and empower future leaders for society.